A PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance and a preparation method thereof

By combining thermally modified acrylic pressure-sensitive adhesive, thermally modified PI film and artificial graphite sheets, a PI/artificial graphite sheet composite film with high thermal conductivity and high insulation performance was prepared, which solved the problem of insufficient thermal conductivity of the existing PI films and achieved efficient heat dissipation and good insulation performance.

CN119177090BActive Publication Date: 2025-03-21WUXI SHUNXUAN NEW MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411700177.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-21
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing polyimide (PI) films have low thermal conductivity and cannot meet the rapid heat dissipation needs of high-power electronic devices. At the same time, artificial graphite sheets have high thermal conductivity but poor insulation performance.

Method used

By combining thermally modified acrylic pressure-sensitive adhesive, thermally modified PI film and artificial graphite sheet, a PI/artificial graphite sheet composite film with high thermal conductivity and high insulation performance was prepared. The mass of the thermally conductive powder added to the thermally modified PI film shall not exceed 32% of the mass of the PI monomer, and the mass of the thermally conductive powder added to the thermally modified acrylic pressure-sensitive adhesive shall not exceed 17% of the mass of the acrylic pressure-sensitive adhesive.

Benefits of technology

It has achieved good insulation performance while having high thermal conductivity, good adhesion, and is not easy to peel off. It is suitable for dealing with problems such as poor heat dissipation of new energy batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177090B_ABST
    Figure CN119177090B_ABST
Patent Text Reader

Abstract

This invention discloses a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation properties, and its preparation method, belonging to the field of polyimide film technology. The method involves first coating a thermally conductive modified acrylic pressure-sensitive adhesive onto the surfaces of a thermally conductive modified PI film and a PET release film, respectively. A PET release film is then attached to the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive. After curing, a PI film and a pure adhesive film are obtained. The PET release film is then removed, and the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure adhesive film are respectively adhered to both sides of an artificial graphite sheet to obtain the PI / artificial graphite sheet composite film. The thermally conductive powder added to the thermally conductive modified PI film does not exceed 32% of the PI monomer mass, and the thermally conductive powder added to the thermally conductive modified acrylic pressure-sensitive adhesive does not exceed 17% of the acrylic pressure-sensitive adhesive mass. The composite film prepared by this invention exhibits excellent high thermal conductivity and high insulation properties, and also has good adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyimide films, and in particular relates to a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance and a preparation method thereof. Background Art

[0002] At present, electronic devices are developing rapidly towards high power, high density and high integration. The integration of high-power chips, wireless charging, Bluetooth and other technologies has caused a sharp increase in the heat generation of electronic devices, seriously affecting the stability, reliability and service life of the equipment. Polyimide (PI) is a polymer material with excellent comprehensive performance. It has low dielectric constant and dielectric loss tangent value, excellent high and low temperature resistance and dimensional stability, as well as excellent radiation resistance, weather resistance and chemical stability. It is widely used in microelectronics, solar cells and gas separation. However, the intrinsic thermal conductivity of PI is low. The thermal conductivity of ordinary polyimide film is only 0.16-0.2W / (m·K), which cannot meet the current flexible displays, folding screens and wearable devices. The requirements of efficient and fast heat conduction / heat dissipation affect the working stability and service life of its electronic devices. At present, the preparation of high thermal conductivity PI materials is divided into two aspects: one is to synthesize intrinsic thermal conductive PI by designing the PI molecular structure and regulating the aggregate structure, and the other is to add high thermal conductivity fillers to PI (or its precursor polyamic acid PAA) to prepare filled PI thermal conductive composite materials.

[0003] Artificial graphite sheets have a high thermal conductivity and are widely used in electronic product heat dissipation. They can timely dissipate the heat energy generated during operation and maintain operating efficiency. However, although artificial graphite sheets have a high thermal conductivity, their insulation performance is very poor.

[0004] Therefore, it is necessary to provide a PI / artificial graphite sheet composite film having both high thermal conductivity and high insulation performance. Summary of the invention

[0005] In view of the above problems existing in the prior art, the first technical problem to be solved by the present invention is to provide a method for preparing a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance, which combines a thermally conductive modified acrylic pressure-sensitive adhesive, a thermally conductive modified PI film and an artificial graphite sheet to prepare a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance. The second technical problem to be solved by the present invention is to provide a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance, which has good insulation performance while having high thermal conductivity, good adhesion, and is not easy to peel off, and is used to deal with the current problems such as poor heat dissipation of new energy batteries.

[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance comprises the following steps: firstly coating a thermally conductive modified acrylic pressure-sensitive adhesive on the surface of a thermally conductive modified PI film and a PET release film respectively, then attaching the PET release film to the side of the thermally conductive modified PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, aging to obtain a PI adhesive film and a pure adhesive film, tearing off the PET release film, and then laminating the side of the PI adhesive film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure adhesive film to the two sides of an artificial graphite sheet respectively to obtain the PI / artificial graphite sheet composite film; wherein the mass of the thermally conductive powder added to the thermally conductive modified PI film does not exceed 32% of the mass of the PI monomer, and the mass of the thermally conductive powder added to the thermally conductive modified acrylic pressure-sensitive adhesive does not exceed 17% of the mass of the acrylic pressure-sensitive adhesive.

[0008] Furthermore, the thermally conductive powder added to the thermally conductive modified PI film is hexagonal boron nitride or aluminum oxide.

[0009] Furthermore, the mass of the thermally conductive powder added to the thermally conductive modified PI film is 20-30% of the mass of the PI monomer.

[0010] Furthermore, the thermally conductive powder added to the thermally conductive modified acrylic pressure-sensitive adhesive is hexagonal boron nitride.

[0011] Furthermore, the mass of the thermally conductive powder added to the thermally conductive modified acrylic pressure-sensitive adhesive is 10-15% of the mass of the acrylic pressure-sensitive adhesive.

[0012] Further, the specific steps are as follows:

[0013] 1) Dissolve aromatic diamine in organic solvent DMAC (dimethylacetamide), add thermal conductive powder, mix well, then add aromatic dianhydride to react to obtain polyamic acid glue, and cast and stretch to obtain thermal conductive modified PI film; wherein the thermal conductive powder is hexagonal boron nitride or aluminum oxide; the viscosity of polyamic acid glue is 30000~80000cp, and the solid content is 18~20%;

[0014] 2) adding hexagonal boron nitride to ethyl acetate, dispersing by ball milling, adding to acrylic pressure-sensitive adhesive, stirring evenly, and obtaining thermally conductive modified acrylic pressure-sensitive adhesive;

[0015] 3) coating the thermally conductive modified acrylic pressure-sensitive adhesive prepared in step 2) on the surface of the thermally conductive modified PI film and the PET release film prepared in step 1), and then attaching the PET release film to the side of the thermally conductive modified PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film;

[0016] 4) The PET release films on the PI film and the pure film obtained in step 3) are torn off, and the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure film are respectively attached to the two sides of the artificial graphite sheet to obtain a PI / artificial graphite sheet composite film.

[0017] Furthermore, in step 1), the aromatic diamine is one or more of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (PDA) and 4,4'-diamino-2,2'-dimethylbiphenyl (M-Tolidine).

[0018] Furthermore, in step 1), the aromatic dianhydride is pyromellitic dianhydride (PMDA) or 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA).

[0019] Furthermore, in step 1), the molar ratio of the aromatic diamine to the aromatic dianhydride is 1:0.9-1, and the amount of DMAC used is 4 times the total mass of the aromatic diamine and the aromatic dianhydride.

[0020] Furthermore, in step 1), the thickness of the thermally conductive modified PI film is 25-36 μm.

[0021] Furthermore, in step 3), the thickness of the artificial graphite sheet is 50-60 μm.

[0022] Furthermore, in step 3), the thickness of the thermally conductive modified acrylic pressure-sensitive adhesive coated on the surface of the thermally conductive modified PI film is 10-15 μm, and the thickness of the thermally conductive modified acrylic pressure-sensitive adhesive coated on the surface of the PET release film is 8-13 μm.

[0023] The method prepares a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance.

[0024] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0025] (1) The PI / artificial graphite sheet composite film prepared by the present invention has high thermal conductivity and good insulation performance, and has good adhesion and is not easy to peel off. The adhesion is ≥5N / 25mm, and it can maintain no breakdown for 60s at 3kV, and the leakage current is less than 0.5mA.

[0026] (2) In the present invention, thermally conductive modified acrylic pressure-sensitive adhesive is adhered to both sides of the artificial graphite sheet, and a thermally conductive modified PI film is adhered to the thermally conductive modified acrylic pressure-sensitive adhesive on one side. The preparation method is simple and convenient and can be mass-produced industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of thermal conductivity testing of the present invention;

[0028] Figure 2This is a cross-sectional view of the PI / artificial graphite sheet composite film prepared in the present invention. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments.

[0030] The thermal conductivity test of the PI / artificial graphite sheet composite film prepared in the following examples is based on the test standard: ASTM D 5470; test equipment: LW 9389; test schematic diagram as shown in Figure 1 shown.

[0031] The leakage current test is based on the standard: GB / T 1408.1-2016; the test equipment: voltage withstand tester; the test method is: take the sample and place it between copper electrodes, apply 3kV alternating current (AC) at both ends of the electrodes, keep it for 60s, and record the current value.

[0032] The 180° peel force test is based on the standard: GB / T 2792-2014, test equipment: PT-501; test method: 1): constant to 25℃, 50% humidity; 2) take 3 samples from the sampling plate, with a film surface of 25mm width and 150mm length, and ensure that the effective length is 100mm; 3) test after standing for 20 minutes, and record the maximum force and minimum force of each data.

[0033] Example 1

[0034] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0035] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, add hexagonal boron nitride, mix well, then add pyromellitic anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and cast and stretched to obtain a thermally conductive modified PI film (25μm); wherein the viscosity of the polyamic acid glue is 42100cp, and the solid content is 20%; the mass of hexagonal boron nitride added is 20% of the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride;

[0036] 2) Add hexagonal boron nitride to ethyl acetate (mass ratio is 1:9), disperse by ball milling (diameter of zirconium beads in the ball mill is 1 mm, speed is 1000 r / min, and ball milling time is 2 h), add to the acrylic pressure-sensitive adhesive, stir evenly, and obtain a thermally conductive modified acrylic pressure-sensitive adhesive; the mass of hexagonal boron nitride added is 15% of the mass of the acrylic pressure-sensitive adhesive;

[0037] 3) coating the thermally conductive modified acrylic pressure-sensitive adhesive prepared in step 2) on the surface of the thermally conductive modified PI film and the PET release film prepared in step 1), and then attaching the PET release film to the side of the thermally conductive modified PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated thermally conductive modified acrylic pressure-sensitive adhesive is 12.5 μm;

[0038] 4) Tear off the PET release film on the PI film and pure film obtained in step 3), and use a laminating machine to laminate the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure film on both sides of the artificial graphite sheet (50 μm) to obtain a PI / artificial graphite sheet composite film. Figure 2 shown.

[0039] Example 2

[0040] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0041] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, add alumina, mix well, then add pyromellitic anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and cast and stretched to obtain a thermally conductive modified PI film (25μm); wherein the viscosity of the polyamic acid glue is 42100cp, and the solid content is 20%; the mass of alumina added is 20% of the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride;

[0042] 2) Add hexagonal boron nitride to ethyl acetate (mass ratio is 1:9), disperse by ball milling (diameter of zirconium beads in the ball mill is 1 mm, speed is 1000 r / min, and ball milling time is 2 h), add to the acrylic pressure-sensitive adhesive, stir evenly, and obtain a thermally conductive modified acrylic pressure-sensitive adhesive; the mass of hexagonal boron nitride added is 15% of the mass of the acrylic pressure-sensitive adhesive;

[0043] 3) coating the thermally conductive modified acrylic pressure-sensitive adhesive prepared in step 2) on the surface of the thermally conductive modified PI film and the PET release film prepared in step 1), and then attaching the PET release film to the side of the thermally conductive modified PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated thermally conductive modified acrylic pressure-sensitive adhesive is 12.5 μm;

[0044] 4) Tear off the PET release film on the PI film and pure film obtained in step 3), and use a laminating machine to laminate the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure film on both sides of the artificial graphite sheet (50 μm) to obtain a PI / artificial graphite sheet composite film. Figure 2 shown.

[0045] Example 3

[0046] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0047] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, mix well, then add pyromellitic anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and the modified PI film (25μm) is obtained by cast stretching; the viscosity of the polyamic acid glue is 45600cp, and the solid content is 20%;

[0048] 2) coating the acrylic pressure-sensitive adhesive on the surface of the PI film and the PET release film prepared in step 1), and then attaching the PET release film to the side of the PI film coated with the acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated acrylic pressure-sensitive adhesive is 12.5 μm;

[0049] 3) The PET release films on the PI film and the pure film obtained in step 3) are torn off, and the side of the PI film coated with the acrylic pressure-sensitive adhesive and the pure film are respectively laminated on the two sides of the artificial graphite sheet (50 μm) using a laminating machine to obtain a PI / artificial graphite sheet composite film.

[0050] Example 4

[0051] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0052] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, add hexagonal boron nitride, mix well, and then add pyromellitic anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and cast stretching is performed to obtain a thermally conductive modified PI film (25μm); wherein, the viscosity of the polyamic acid glue is 42300cp, and the solid content is 20%; the mass of hexagonal boron nitride added is 20% of the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride;

[0053] 2) coating the thermally conductive modified PI film and the PET release film prepared in step 1) with an acrylic pressure-sensitive adhesive, and then attaching the PET release film to the side of the thermally conductive modified PI film coated with the acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated acrylic pressure-sensitive adhesive is 12.5 μm;

[0054] 3) The PET release films on the PI film and the pure film obtained in step 2) were torn off, and the side of the PI film coated with the acrylic pressure-sensitive adhesive and the pure film were respectively laminated on the two sides of the artificial graphite sheet (50 μm) using a laminating machine to obtain a PI / artificial graphite sheet composite film.

[0055] Example 5

[0056] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0057] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, add hexagonal boron nitride, mix well, and then add pyromellitic anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and cast stretching is performed to obtain a thermally conductive modified PI film (25μm); wherein, the viscosity of the polyamic acid glue is 41900cp, and the solid content is 20%; the mass of hexagonal boron nitride added is 30% of the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride;

[0058] 2) coating the thermally conductive modified PI film and the PET release film prepared in step 1) with an acrylic pressure-sensitive adhesive, and then attaching the PET release film to the side of the thermally conductive modified PI film coated with the acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated acrylic pressure-sensitive adhesive is 12.5 μm;

[0059] 3) The PET release films on the PI film and the pure film obtained in step 2) were torn off, and the side of the PI film coated with the acrylic pressure-sensitive adhesive and the pure film were respectively laminated on the two sides of the artificial graphite sheet (50 μm) using a laminating machine to obtain a PI / artificial graphite sheet composite film.

[0060] Example 6

[0061] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0062] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, add hexagonal boron nitride, mix well, and then add pyromellitic anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and cast stretching is performed to obtain a thermally conductive modified PI film (25μm); wherein, the viscosity of the polyamic acid glue is 38700cp, and the solid content is 20%; the mass of hexagonal boron nitride added is 50% of the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride;

[0063] 2) coating the thermally conductive modified PI film and the PET release film prepared in step 1) with an acrylic pressure-sensitive adhesive, and then attaching the PET release film to the side of the thermally conductive modified PI film coated with the acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated acrylic pressure-sensitive adhesive is 12.5 μm;

[0064] 3) The PET release films on the PI film and the pure film obtained in step 2) were torn off, and the side of the PI film coated with the acrylic pressure-sensitive adhesive and the pure film were respectively laminated on the two sides of the artificial graphite sheet (50 μm) using a laminating machine to obtain a PI / artificial graphite sheet composite film.

[0065] Example 7

[0066] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0067] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, mix well, then add pyromellitic acid anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic acid anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic acid anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and cast and stretched to obtain a PI film (25μm); wherein the viscosity of the polyamic acid glue is 46300cp, and the solid content is 20%;

[0068] 2) Add hexagonal boron nitride to ethyl acetate (mass ratio is 1:9), disperse by ball milling (diameter of zirconium beads in the ball mill is 1 mm, speed is 1000 r / min, and ball milling time is 2 h), add to the acrylic pressure-sensitive adhesive, stir evenly, and obtain a thermally conductive modified acrylic pressure-sensitive adhesive; the mass of hexagonal boron nitride added is 15% of the mass of the acrylic pressure-sensitive adhesive;

[0069] 3) coating the thermally conductive modified acrylic pressure-sensitive adhesive prepared in step 2) on the surface of the PI film and the PET release film prepared in step 1), respectively, and then attaching the PET release film to the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated thermally conductive modified acrylic pressure-sensitive adhesive is 12.5 μm;

[0070] 4) Tear off the PET release films on the PI film and pure film obtained in step 3), and laminate the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure film on both sides of the artificial graphite sheet (50 μm) using a laminating machine to obtain a PI / artificial graphite sheet composite film.

[0071] Example 8

[0072] The preparation method of PI / artificial graphite sheet composite film is as follows:

[0073] 1) Dissolve 4,4'-diaminodiphenyl ether in an organic solvent DMAC, mix well, then add pyromellitic anhydride to react (the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic anhydride is 1:0.992, and the amount of DMAC used is 4 times the total mass of 4,4'-diaminodiphenyl ether and pyromellitic anhydride), the temperature is 60°C, and polyamic acid glue is obtained, and cast and stretched to obtain a PI film (25μm); wherein the viscosity of the polyamic acid glue is 47100cp, and the solid content is 20%;

[0074] 2) Add hexagonal boron nitride to ethyl acetate (mass ratio is 1:9), disperse by ball milling (diameter of zirconium beads of ball mill is 1 mm, speed is 1000 r / min, and ball milling time is 2 h), add to acrylic pressure-sensitive adhesive, stir evenly, and obtain thermally conductive modified acrylic pressure-sensitive adhesive; the mass of hexagonal boron nitride added is 20% of the mass of acrylic pressure-sensitive adhesive;

[0075] 3) coating the thermally conductive modified acrylic pressure-sensitive adhesive prepared in step 2) on the surface of the PI film and the PET release film prepared in step 1), respectively, and then attaching the PET release film to the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; wherein the thickness of the coated thermally conductive modified acrylic pressure-sensitive adhesive is 12.5 μm;

[0076] 4) Tear off the PET release films on the PI film and pure film obtained in step 3), and laminate the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure film on both sides of the artificial graphite sheet (50 μm) using a laminating machine to obtain a PI / artificial graphite sheet composite film.

[0077] The performance of the composite membrane prepared in the above examples was tested, and the results are shown in Table 1 below.

[0078] Table 1 Performance test results of the composite membranes prepared in Examples 1 to 8

[0079]

[0080] Table 1 shows the performance test results of the composite films prepared in Examples 1 to 8. It can be seen from the table that, from the perspective of thermal conductivity, the addition of thermal conductive powder (boron nitride or aluminum oxide) will increase the thermal conductivity. The greater the addition amount, the higher the thermal conductivity. However, as the addition amount increases, the leakage current will also increase. If the addition amount is too high, the leakage current will be greater than 0.5mA at AC 3kV. Therefore, the addition amount of thermal conductive powder in the PI of Example 6 is too much, which affects the performance of the composite film. The adhesion of the acrylic pressure-sensitive adhesive film is also related to the addition amount of thermal conductive filler. When the addition amount reaches 20%, the 180° peeling force is less than 5N, which is easy to peel off. However, the thermal resistance of the acrylic acid pressure-sensitive adhesive film will be large, and the thermal conductivity modification of the acrylic acid pressure-sensitive adhesive film will affect the overall thermal conductivity. In summary, Examples 1 and 2 have both thermal conductivity, insulation performance (leakage current) and adhesion. Compared with Examples 1 and 2, the leakage current of aluminum oxide will be greater than that of boron nitride, but the thermal conductivity of the two is close.

Claims

1. A method for preparing a PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance, characterized in that: First, the thermally conductive modified acrylic pressure-sensitive adhesive is coated on the surface of the thermally conductive modified PI film and the PET release film respectively, and then the PET release film is attached to the side of the thermally conductive modified PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, and the PI film and the pure adhesive film are obtained after aging, and the PET release film is torn off, and then the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure adhesive film are respectively attached to the two sides of the artificial graphite sheet to obtain the PI / artificial graphite sheet composite film; wherein the thermally conductive powder added to the thermally conductive modified PI film is hexagonal boron nitride or aluminum oxide; the mass of the thermally conductive powder added to the thermally conductive modified PI film is 20-30% of the mass of the PI monomer; the thermally conductive powder added to the thermally conductive modified acrylic pressure-sensitive adhesive is hexagonal boron nitride, and the mass of the thermally conductive powder added to the thermally conductive modified acrylic pressure-sensitive adhesive is 10-15% of the mass of the acrylic pressure-sensitive adhesive.

2. The method for preparing the PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance according to claim 1, characterized in that: The specific steps are as follows: 1) Dissolve aromatic diamine in organic solvent DMAC, add thermal conductive powder, mix well, then add aromatic dianhydride to react, obtain polyamic acid glue, and cast and stretch to obtain thermal conductive modified PI film; wherein the thermal conductive powder is hexagonal boron nitride or aluminum oxide; the viscosity of polyamic acid glue is 30000~80000cp, and the solid content is 18~20%; 2) adding hexagonal boron nitride to ethyl acetate, dispersing by ball milling, adding to acrylic pressure-sensitive adhesive, stirring evenly, and obtaining thermally conductive modified acrylic pressure-sensitive adhesive; 3) coating the thermally conductive modified acrylic pressure-sensitive adhesive prepared in step 2) on the surface of the thermally conductive modified PI film and the PET release film prepared in step 1), and then attaching the PET release film to the side of the thermally conductive modified PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive, and curing them at 50° C. for 3 days to obtain a PI adhesive film and a pure adhesive film; 4) The PET release films on the PI film and the pure film obtained in step 3) are torn off, and the side of the PI film coated with the thermally conductive modified acrylic pressure-sensitive adhesive and the pure film are respectively attached to the two sides of the artificial graphite sheet to obtain a PI / artificial graphite sheet composite film.

3. The method for preparing the PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance according to claim 2, characterized in that: In step 1), the thickness of the thermally conductive modified PI film is 25-36 μm.

4. The method for preparing the PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance according to claim 2, characterized in that: In step 4), the thickness of the artificial graphite sheet is 50-60 μm.

5. The method for preparing the PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance according to claim 2, characterized in that: In step 3), the thickness of the thermally conductive modified acrylic pressure-sensitive adhesive coated on the surface of the thermally conductive modified PI film is 10-15 μm, and the thickness of the thermally conductive modified acrylic pressure-sensitive adhesive coated on the surface of the PET release film is 8-13 μm.

6. A PI / artificial graphite sheet composite film with high thermal conductivity and high insulation performance prepared by the method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Graphite sheet heat dissipation patch and production process thereof

    CN115521726A